Accessory proteins for heterotrimeric G-proteins in the kidney - Park, Frank (Frontiers in Physiology, 2015)
Heterotrimeric G-proteins play a fundamentally important role in regulating signal transduction pathways in the kidney. Accessory proteins are being identified as direct binding partners for heterotrimeric G-protein α or βγ subunits to promote more diverse mechanisms by which G-protein signaling is controlled. In some instances, accessory proteins can modulate the signaling magnitude, localization, and duration following the activation of cell membrane-associated receptors. Alternatively, accessory proteins complexed with their G-protein α or βγ subunits can promote non-canonical models of signaling activity within the cell. In this review, we will highlight the expression profile, localization and functional importance of these newly identified accessory proteins to control the function of select G-protein subunits under normal and various disease conditions observed in the kidney.